Nano-technology as an eco-friendly approach in agriculture - Roy, Barnali; Pal, Amit Kumar (Plant Science Today, 2025)
Global food security is now the most challenging issue due to the limited natural resources, low productivity of food crops in the agricultural sector, rapid climate changes and huge population growth. Researchers are trying to adopt newer innovations and technologies to increase the production of food crops to meet the demand. Nanotechnology is one of the most challenging technologies that could enhance the productivity of crops in sustainable agriculture, giving importance to nano-fertilizers, nano-pesticides, nano-biosensors and nano-material-based remediation strategies. The physical and chemical processes to produce nanoparticles (NP) have a detrimental effect on the ecosystem. Thus, green synthesis of NPs using various microorganisms offers a more promising and sustainable alternative. Nanotechnology is very promising as it has many potential benefits like improvement of food quality, minimization of agricultural inputs and enrichment of plants by absorbing nutrients from the soil. Nanoparticles can be used as nanofertilizers, distinct agrochemical carriers and site-targeted or regulated nutrition delivery with improved crop protection. The potential of nanomaterials offers a new green revolution in sustainable agriculture.